The Roles of Community Policing for Community Security and Peace Building: The Case of Asella Town Administration - Tafese, Gosa Setu (2020)
Community policing is the most means of reacting to incidents and insecurity before it happens and improving social environment as well as reducing fear of crime. Despite its vital roles in maintaining peace and security for the local community, there is no adequate literature on the roles of community policing for community security and peace building. This implies that there is little known about the roles of community policing in Asella Town administration and as a result this study aimed to assess the roles of community policing for community security and peace building in Asella Town Administration. To conduct this research qualitative research approach was used. For this purpose, data collected through different data collection mechanism including key informants, focus group discussion and participant observation. were analyzed through thematic data analysis approach. The findings of this research indicate that, community policing brings the police officers and the community of Asella town together to deter crime and promote community security. It also increased the perceptions of safety and reduced anti-social behavior. It also empowered the community of the town to take charge of their security needs. It also increased the satisfaction of police officers towards their work in community. The collective security action of community policing in the Asella town involved various community members such as elders, youth and religious organization. Community policing needs to be practiced in a systematic way to demonstrate better results in maintaining peace and security issues. Community meetings on community policing must be take place regularly in order to involve more community members in community policing activities. Keywords: Community Policing, Community Security and Stability, Asella Town DOI: 10.7176/PPAR/10-10-06 Publication date:October 31st 202